Design and Analysis of Asymmetric Involute Gear - Li Jianguo; Zhang Haiwei; Chen Zhenguo (Jixie chuandong)
The asymmetric involute gear tooth is designed,a collaborative coordinate of rack cutter,gear blanks and frame is built,the end face of rack cutter is designed,the tooth profile equation is determined,the tooth profile is simulated.The stress of single contact point to active small gear is analyzed,four force pressure angle combination are calculated using the formula method on 20° /20°,25° /20°,30° /20° and 35° /20°,the result is verified by using the finite element method,the comparative analysis results show that work with large pressure angle tooth surface can effectively improve the contact strength and bending strength of the gear.